2022
DOI: 10.1177/18333583221078377
|View full text |Cite
|
Sign up to set email alerts
|

The suitability of government health information assets for secondary use in research: A fit-for-purpose analysis

Abstract: Background Governments have responsibility for ensuring the quality and fitness-for-purpose of personal health data provided to them. While these health information assets are used widely for research, this secondary usage has received minimal research attention. Objective This study aimed to investigate the secondary uses, in research, of population health and administrative datasets (information assets) of the Department of Health (DoH), Victoria, Australia. The objectives were to (i) identify research based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 33 publications
(48 reference statements)
1
14
0
Order By: Relevance
“…Riley et al’s. [ 55 ] documentary analysis of the availability of website information-categories involving the within-scope datasets identified that almost 70% of dataset websites contained information on the access process. Our survey demonstrated, however, that less than half of the respondents reported the process for requesting data access to be easy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Riley et al’s. [ 55 ] documentary analysis of the availability of website information-categories involving the within-scope datasets identified that almost 70% of dataset websites contained information on the access process. Our survey demonstrated, however, that less than half of the respondents reported the process for requesting data access to be easy.…”
Section: Discussionmentioning
confidence: 99%
“…Our survey demonstrated, however, that less than half of the respondents reported the process for requesting data access to be easy. Given the documentary analysis findings [ 55 ], we would expect a higher proportion of survey respondents to find the access process easier if it was only related to documentation availability. In our survey we did not ask reasons why the process for requesting access was difficult; however, other researchers have reported ease of access can be related to factors such as data type (e.g., identifying versus aggregated), the access portal (e.g., openness), external factors (e.g., legal/legislative compliance issues), public engagement (e.g., acceptability of data release) [ 56 ], or resourcing issues (e.g., cost of infrastructure to sustain sharing and reuse of government data) [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) What were the applications of ICD-10 and ICD-10-AM Australian-coded data in peer-reviewed research published in 2012-2022? (2) What were the purposes of ICD-10 and ICD-10-AM coded data within this research context, as classified according to a pre-existing, modified taxonomy of data use framework (Riley et al, 2022)?…”
Section: Research Questionsmentioning
confidence: 99%
“…Conversely, creators of clinical documentation may have limited appreciation of the wide-ranging impact of CDI and its coded derivatives, including for purposes of research and epidemiology. The potential dangers of researchers using data inappropriately for secondary purposes was highlighted by Riley et al (2023b) who conducted a "fit for purpose" analysis of government health information assets. While the authors verified that the health information assets they examined had been appropriately used for secondary purposes, they nevertheless called for greater transparency in the secondary use of data, to safeguard public trust in the collection, storage and management of personal and sensitive information.…”
Section: Virtual Special Issue On CDImentioning
confidence: 99%